A review of computational fluid dynamics (CFD) simulations of the wind flow around buildings for urban wind energy exploitation. Issue 180 (September 2018) - Toja-Silva, Francisco; Kono, Takaaki; Peralta, Carlos; Lopez-Garcia, Oscar; Chen, Jia
Abstract: This article presents a review on computational fluid dynamics (CFD) applied to urban wind energy exploitation. The content comprises technical CFD aspects relevant for this application and the current state-of-the-art in building aerodynamics applied to urban wind energy. The majority of studies (more than 50% of the respective criteria) used Reynolds-averaged Navier-Stokes (RANS) turbulence models, the commercial solver ANSYS, simulated a full-scale geometry and studied an isolated building. For RANS, at least second order-accurate discretization schemes must be used, to improve turbulence kinetic energy prediction. In large-eddy simulation (LES) studies, a blending scheme is often needed to avoid numerical instability. Urban wind flow is very complex (i.e. detachment, stagnation), and rigorous validation and verification processes are needed, because only sophisticated turbulence models are able to yield acceptable results. The building-roof shape was optimized for the wind energy exploitation attending to both turbulence intensity and wind velocity. Conventional roof and roof edge shapes were studied, as well as the compatibility with the installation of solar panels. Wind turbines sitting was also discussed. Few simulations of wind turbines installed on building roofs were conducted using wind turbine models, whereas real geometries of vertical axis wind turbines were simulated and optimized. Highlights: A review on CFD applied to urban wind energy exploitation is presented. Technical issues about turbulence modelling, numerical schemes and meshing are included. Roof shape, roof-edge shape and the compatibility with solar energy are discussed. Cited works comprise isolated buildings, simplified surroundings and real cities. CFD simulations of wind turbine models and real geometries on buildings roofs are referenced.